An efficient decay model for studying the luminous flux behavior of phosphor-converted white light-emitting diodes - Nguyen, Quang-Khoi; Nguyen, Thi-Phuong-Loan; Huynh, Van-Tuan; Phan, Nguyet-Thuan; Nguyen, Huynh-Tuan-Anh (Photonics Letters of Poland, 2023)
We proposed a new idea for testing the thermal decay of light source under the effect of heat where the lux meter is used rather than using the integrating sphere and the thermal camera is used rather than thermocouple. The thermal decay behavior of the light is detected by using the lux meter. The thermal camera can be used to provide the temperature value as well as the temperature distribution of the measured surface which is more convenient than by using the thermocouple. This fitting model is useful for finding out the decay rate of output light under thermal effect. Full Text: PDF References E.F. Schubert and J. K. Kim, "Solid-State Light Sources Getting Smart", Science 308, 1274-1278 (2005). CrossRef E.F. Schubert, Light-emitting diodes (Cambridge University Press, 2006). CrossRef N. Narendran and Y. Gu, "Life of LED-based white light sources", J. Disp. Technol. 1, 167-171 (2005). CrossRef Y.Y. Chang, Z.Y. Ting, C.Y. Chen, T.H. Yang, and C.C. Sun, "Design of Optical Module With High Stability, High Angular Color Uniformity, and Adjustable Light Distribution for Standard Lamps", J. Disp. Technol. 10, 223-227 (2014). CrossRef C.C. Sun, C.Y. Chen, C.C. Chen, C.Y. Chiu, Y.N. Peng, Y.H. Wang, T.H. Yang, T.Y. Chung, and C.Y. Chung, "High uniformity in angular correlated-color-temperature distribution of white LEDs from 2800K to 6500K", Opt. Express 20, 6622-6630 (2012). CrossRef C.C. Sun, Q.K. Nguyen, T.X. Lee, S.K. Lin, C.S. Wu, T.H. Yang, and Y.W. Yu. "Active thermal-fuse for stopping blue light leakage of white light-emitting diodes driven by constant current", Sci. Rep. 12, 12433 (2022). CrossRef Q.K. Nguyen, Y.J. Lin, C. Sun, X.H. Lee, S.K. Lin, C.S. Wu, T.H. Yang, T.L. Wu, T.X. Lee, C.H. Chien, Y.W. Yu & C.C. "GaN-based mini-LED matrix applied to multi-functional forward lighting", Sun. Sci. Rep. 12, 6444 (2022). CrossRef T.T. N. Le, C.T. Liao, S.K. Lin, C.S. Wu, Q.K. Nguyen, T.H. Yang, Y.W. Yu, and C.C. Sun. "Study of banana preservation extension by UVC radiation in precise monitoring LED irradiation cavity", Sci. Rep. 12, 21352 (2022). CrossRef N. Narendran, Y. Gu. "Life of LED-based white light sources", J. Disp. Technol. 1, 167 (2005). CrossRef G.H. Xiao, W.J. Du, Z.Y. Wang, G.L. Chen, L.H. Zhu , Y.L. Gao , Z. Chen , Z.Q. Guo, Y.J. Lu. "Two-Dimensional Transient Temperature Distribution Measurement of GaN Light-Emitting Diode Using High Speed Camera", IEEE J. Electron Devices Soc. 9, 663-666 (2021). CrossRef N. Han, T.V. Cuong, M. Han, B.D. Ryu, S. Chandramohan, J.B. Park, J.H. Kang, Y.J. Park, K.B. Ko, H.Y. Kim, H.K. Kim, J.H. Ryu, Y.S. Katharria, C.J. Choi, C.H. Hong. "Improved heat dissipation in gallium nitride light-emitting diodes with embedded graphene oxide pattern", Nat Commun 4, 1452 (2013) CrossRef M. Cai, D.G. Yang, K.M. Tian, P. Zhang, X.P. Chen, L.L. Liu, G.Q. Zhang. "Step-stress accelerated testing of high-power LED lamps based on subsystem isolation method", Microelectron Reliab 55, 1784 (2015). CrossRef K.S. Chang, S.C. Yang, J.Y. Kim, M.H. Kook, S.Y. Ryu, H.Y. Choi, G.H. Kim. "Precise Temperature Mapping of GaN-Based LEDs by Quantitative Infrared Micro-Thermography", Sensors 12, 4648-4660 (2012). CrossRef Y. Gao, J. Jin, Y.J. Ruan, Y.L. Gao, L.H. Zhu, Z.Q. Guo, Y. Lin, Z. Chen, and Y.J. Lu. "Two-dimensional temperature distribution measurement of light-emitting diodes by micro-hyperspectral imaging-based reflected light method", Optics Express 27, 7945 (2019). CrossRef B.L. Liang , Z.L. Wang , C. Qian , Y. Ren , B. Sun , D.Z. Yang , Z. Jing and J.J. Fan. "Investigation of Step-Stress Accelerated Degradation Test Strategy for Ultraviolet Light Emitting Diodes", Materials 12, 3119 (2019). CrossRef J. Hegedüs, G. Hantos, A. Poppe. "Lifetime Modelling Issues of Power Light Emitting Diodes", Energies 13, 3370 (2020). CrossRef A. Alexeev, J.P. Linnartz, G. Onushkin, K. Arulandu, G. Martin. "Dynamic response-based LEDs health and temperature monitoring", Measurement 156, 107599 (2020). CrossRef K. Paisnik, G. Rang and T. Rang. "Life-time characterization of LEDs", Est J. Eng 17, 241 (2011). CrossRef A. Vaskuri, P. Kärhä, H. Baumgartner, O. Kantamaa, T. Pulli, T. Poikonen, E. Ikonen. "Relationships between junction temperature, electroluminescence spectrum and ageing of light-emitting diodes", Metrologia 55, S86 (2018). CrossRef